PENGEMBANGAN GAME KAHOOT! BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SEKOLAH DASAR - Qonita Afriyani; Munaris; Rangga Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
games in improving students' critical thinking skills in the Indonesian language subject of grade IV students of SD Negeri 2 Perumnas Way Kandis. The development model used was 4D involving 31 students. The results showed that conventional methods caused boredom and saturation in learning, while local wisdom-based kahoot! games increased student engagement and understanding. Validation by material, language, and media experts ensured the feasibility of local wisdom-based kahoot! games with several revisions to improve the clarity of the display and language. The t-test showed a significant difference between the experimental class and the control class (Sig. 2-tailed = 0.000), N-Gain in the experimental class was 62.96% while in the control class it was 38.99% indicating high effectiveness. The average value increased from 58.25 (pre-test) to 84.77 (post-test). Thus, the kahoot! based on local wisdom has been proven to be an innovative solution in improving students' critical thinking skills.